2014
DOI: 10.1038/bjc.2014.361
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of exhaled breath for diagnosing head and neck squamous cell carcinoma: a feasibility study

Abstract: Background:Squamous cell carcinoma of the head and neck (HNSCC) are wide-spread cancers that often lead to disfigurement and loss of important functions such as speech and ingestion. To date, HNSCC has no adequate method for early detection and screening.Methods:Exhaled breath samples were collected from 87 volunteers; 62 well-defined breath samples from 22 HNSCC patients (larynx and pharynx), 21 patients with benign tumours (larynx and pharynx) and 19 healthy controls were analysed in a dual approach: (i) che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 38 publications
4
106
2
1
Order By: Relevance
“…VOCs related to diseases like diabetes mellitus and uraemia in breath Other evidence that VOC profiles in exhaled breath can be used to detect diseases has been shown by Phillips et al for lung and breast cancer [24]. A pilot study of analysis of air exhaled by HNSCC patients using an array of five gold nanoparticle sensors and gas chromatography has shown promising results [1,2]. VOCs related to diseases like diabetes mellitus and uraemia in breath Other evidence that VOC profiles in exhaled breath can be used to detect diseases has been shown by Phillips et al for lung and breast cancer [24].…”
Section: Resultsmentioning
confidence: 99%
“…VOCs related to diseases like diabetes mellitus and uraemia in breath Other evidence that VOC profiles in exhaled breath can be used to detect diseases has been shown by Phillips et al for lung and breast cancer [24]. A pilot study of analysis of air exhaled by HNSCC patients using an array of five gold nanoparticle sensors and gas chromatography has shown promising results [1,2]. VOCs related to diseases like diabetes mellitus and uraemia in breath Other evidence that VOC profiles in exhaled breath can be used to detect diseases has been shown by Phillips et al for lung and breast cancer [24].…”
Section: Resultsmentioning
confidence: 99%
“…In a complementary analysis, mass spectrometry analysis showed major differences in the concentrations of more than 13 different VOCs between the three subgroups [58]. In a more recent study, similar sensor future science group Review Nakhleh, Broza & Haick arrays provided accurate predictive models for distinguishing head and neck squamous cell carcinoma (HNSCC) from healthy states, HNSCC from benign tumors and benign tumors from healthy states [59]. Two additional predictive models allowed classification of HNSCC according to site and stage.…”
Section: Head and Neck Cancermentioning
confidence: 98%
“…Two additional predictive models allowed classification of HNSCC according to site and stage. Patient classification was possible irrespective of the gender and tobacco consumption of the individual participants, which constitute important confounding as well as risk factors for HNSCC [59].…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…In addition, dimethyl disulfide, decamethylcyclopentasiloxane (D5), and p‐xylene (PX) have been reported as gas phase biomarkers that decrease after surgery . Ethanol, 2‐propenenitrile and undecane have also been identified as exhaled gas biomarkers that could distinguish laryngeal and pharyngeal head and neck squamous cell carcinoma from benign tumors and from healthy subjects …”
Section: Potential Breath Biomarkers Of Hncmentioning
confidence: 99%
“…In oral squamous cell carcinoma, a recent study used EBA and found three compounds (benzaldehyde, 3,7‐dimethylundecane, and butyl acetate) that have a relationship with pathological parameters of these cancers . The methods used for EBA of HNC patients so far include gas chromatography‐mass spectrometry, various nanomaterial‐based sensors and chemical ionization mass spectrometry …”
Section: Exhaled Breath Analysis As a Diagnostic Tool In Head And Necmentioning
confidence: 99%